Anaerobic Respiration Using a Complete Oxidative TCA Cycle Drives Multicellular Swarming in Proteus mirabilis - Christopher J. Alteri (American Society for Microbiology, 2012)
ABSTRACT Proteus mirabilis rapidly migrates across surfaces using a periodic developmental process of differentiation alternating between short swimmer cells and elongated hyperflagellated swarmer cells. To undergo this vigorous flagellum-mediated motility, bacteria must generate a substantial proton gradient across their cytoplasmic membranes by using available energy pathways. We sought to identify the link between energy pathways and swarming differentiation by examining the behavior of defined central metabolism mutants. Mutations in the tricarboxylic acid (TCA) cycle (fumC and sdhB mutants) caused altered patterns of swarming periodicity, suggesting an aerobic pathway. Surprisingly, the wild-type strain swarmed on agar containing sodium azide, which poisons aerobic respiration; the fumC TCA cycle mutant, however, was unable to swarm on azide. To identify other contributing energy pathways, we screened transposon mutants for loss of swarming on sodium azide and found insertions in the following genes that involved fumarate metabolism or respiration: hybB, encoding hydrogenase; fumC, encoding fumarase; argH, encoding argininosuccinate lyase (generates fumarate); and a quinone hydroxylase gene. These findings validated the screen and suggested involvement of anaerobic electron transport chain components. Abnormal swarming periodicity of fumC and sdhB mutants was associated with the excretion of reduced acidic fermentation end products. Bacteria lacking SdhB were rescued to wild-type pH and periodicity by providing fumarate, independent of carbon source but dependent on oxygen, while fumC mutants were rescued by glycerol, independent of fumarate only under anaerobic conditions. These findings link multicellular swarming patterns with fumarate metabolism and membrane electron transport using a previously unappreciated configuration of both aerobic and anaerobic respiratory chain components. IMPORTANCE Bacterial locomotion and the existence of microbes were the first scientific observations that followed the invention of the microscope. A bacterium can swim through a fluid environment or coordinate motion with a group of bacteria and swarm across a surface. The flagellar motor, which propels the bacterium, is fueled by proton motive force. In contrast to the physiology that governs swimming motility, much less is known about the energy sources required for multicellular swarming on surfaces. In this study, we used Proteus mirabilis as a model organism to study vigorous swarming behavior and genetic and biochemical approaches to define energy pathways and central metabolism that contribute to multicellular motility. We found that swarming bacteria use a complete aerobic tricarboxylic acid (TCA) cycle but do not respire oxygen as the terminal electron acceptor, suggesting that multicellular cooperation during swarming reduces the amount of energy required by individual bacteria to achieve rapid motility.